Pelapisan Permukaan Stainless Steel 316L Menggunakan Hidroksiapatit Dengan Metode Deposisi Elektroforesis - Muhamamad Rizky Zuriadi; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite (HA) is ceramic that can be used as bone implants and teeth. However hydroxyapatite has a weakness in terms of its weak physical properties so it need to be modified with hydroxyapatite coating on a metal surface. The purpose of this study is to determine the influence of pH and concentration of hydroxyapatite. Hydroxyapatite was coated on the surface of Stainless steel using electrophoretic deposition method. HA suspension with concentration 0,025 and 0,075M were made by mixing 0,0425 and 1,3575 gr with ethanol and then set to pH 3,4 and 10 by adding HNO3 and NH4OH. Subsequently, the coating process was carried out by dipping Stainless steel and carbon electrode into hydroxyapatite suspension. The hydroxyapatite suspension was electrified with a voltage of 60 V for 2 minutes. Then hydroxyapatite coating was calcined with temperature of 800o C for 2 hours. SEM analysis shown that the thickness of HA deposits was 32-52 μm at HA concentration of 0,025 M and it increased to 42-57 μm at HA concentration of 0,075 M. The thickness of HA deposists was 60-80 μm at pH 3 and it decreased to 40-50 μm at pH 10. corrosion rate analysis shown that HA coating can reduce corrosion rate of stainless steel. FTIR analysis showed PO43-, OH, and H2O groups that indicates the content of hydroxyapatite from sample. Keywords : coating, electrophoretic deposition, hydroxyapatite, stainless steel